Resveratrol attenuates pulmonary fibrosis by inhibiting alveolar epithelial senescence via targeting SASP-related proteins: an integrated bioinformatics-experimental study - Zuo, Biao; Yuan, Su; Luo, Chen; Du, Xu-Qin; Wu, Yong-Can; Shi, Li-Peng; Chen, Jin-Xin; Chen, Bo-Tao; Zhou, Jie; Ren, Yi (Frontiers in Pharmacology, 2025)
BackgroundPulmonary fibrosis (PF) is a progressive and fatal interstitial lung disease with limited treatment options. Premature senescence of alveolar epithelial type II cells (AT2 cells) plays a critical role in PF pathogenesis. This study aimed to identify natural compounds targeting senescence-related pathways for PF treatment.MethodsAn integrated approach was implemented, combining bioinformatics, artificial intelligence (AI)-assisted molecular docking, ADMET (absorption, distribution, metabolism, excretion, and toxicity) profiling, and experimental validation. Core targets associated with aging-related pulmonary fibrosis (PF) were identified via database mining (GeneCards and AgingAtlas) and protein-protein interaction (PPI) network analysis. Natural compounds were screened using the HERB database, and resveratrol (RES) was selected due to its multi-target activity and favorable ADMET characteristics. The efficacy of RES was evaluated through in vitro experiments using bleomycin (BLM)-induced senescent A549 alveolar epithelial cells and in vivo studies in a BLM-induced PF mouse model (C57BL/6J). Molecular docking simulations were performed to predict the binding affinity between RES and key targets, including SERPINE1, MMP2, and IL-6.ResultsBioinformatics identified 322 aging-related PF targets, with TP53, AKT1, STAT3, JUN, and NFKB1 as core regulators. Resveratrol was selected as a top candidate modulating all five core targets and exhibiting optimal drug-likeness. Molecular docking and dynamics simulations confirmed strong binding affinity between RES and key senescence-associated proteins (SERPINE1: −8 kcal/mol; MMP2: −7.5 kcal/mol; IL-6: −7.1 kcal/mol). In vitro, RES (10–40 μM) significantly suppressed bleomycin-induced senescence in A549 cells, reducing SA-β-Gal activity and downregulating SERPINE1, MMP2, and IL6 expression. In vivo, RES treatment (20–80 mg/kg, 21 days) attenuated bleomycin-induced PF in mice, improving weight loss, reducing alveolar damage, inflammation, and collagen deposition (Masson’s trichrome) in a dose-dependent manner.ConclusionResveratrol effectively inhibits alveolar epithelial cell senescence and ameliorates pulmonary fibrosis, likely by targeting key senescence-associated pathways (e.g., SERPINE1, MMP2, IL-6). This study provides a promising transdisciplinary strategy for anti-fibrotic drug discovery and highlights RES as a potential therapeutic candidate for PF.